Pengaruh industri kecil terhadap pertumbuhan ekonomi di Provinsi Jambi - Febriani Sitanggang; Purwaka Hari Prihanto; Etik Umiyati (e-Journal Perdagangan Industri dan Moneter, 2019)
This study aims to determine the effect of the number of business units, investment, and labor on economic growth in Jambi Province in 2001-2017. This type of research is descriptive quantitative. The use of secondary data from the publication of the Central Statistics Agency of Jambi Province in the form of time series data, namely Economic Growth, number of small industrial business units, small industrial investment, small industrial workforce. The results showed that, from the results of the t-test, it can be concluded that for each small industrial business unit variable, the number of small industrial business units and small industrial workers has a significant effect on economic growth. The results of the coefficient of determination test (R²) show that the ability of the independent variables (small industrial business units, small industrial investment and small industrial workers) in explaining the dependent variable (economic growth) is 98.69 percent. In comparison, the variable others explain the remaining 1.31 percent outside the model. Keywords:  Economic growth, Business units, Labor, Investment